Breaking Barriers: Advancing Gender Equity in Geriatric Medicine. Results of an International Survey - Anna Rudzińska; Ian Perera; Sofia Duque; Marina Kotsani; Robert Kupis; Jerzy Gąsowski; Mirko Petrovic; Anne Ekdahl; Karolina Piotrowicz (Journal of General Internal Medicine, 2026)
Abstract Introduction Although there are more women than men working in the healthcare system in Europe, reports of gender-related inequities within the healthcare workforce are still emerging. Our study aimed to gather insights from women, representing different healthcare professions, who work in the field of geriatric medicine and gerontology, to better understand their perspectives and experiences. Methods In February 2025, we distributed an anonymous online survey to women affiliated with the PROGRAMMING COST Action 21122. We summarised the quantitative data and performed an analysis of the responses to the open-ended questions. Results We collected 53 answers (mean (SD) age of 41.6 (9.3) years old) to the survey from individuals representing 23 countries. Most women pointed out at least one challenge they have faced as women working in the field of geriatric medicine, with work-life balance and family responsibilities being indicated most often. Three main topics emerged in the qualitative analysis: gender disparities in promotion and career advancement, impact of family responsibilities on training completion, and scientific and professional recognition. The respondents pointed out coping strategies that could be used to overcome gender barriers. Over 60% of respondents highlighted internal coping resources, such as personal resilience and only 10% mentioned institutional policies. Conclusion Women face some significant challenges in personal development in geriatric medicine consequent on their gender and social role assigned, with the most attention being given to balancing family and work duties, and advancement opportunities.